Beyond Internet Access: a study of social and cultural practices in LAN Houses - Nemer, David (AoIR Selected Papers of Internet Research, 2013)
LAN Houses, for-profit internet cafés, have been one of the main strategies from the Brazilian government to promote the internet access in marginalized areas. Although the internet is the main purpose of such businesses, LAN Houses provide an important space for Brazil’s urban poor areas, known as favelas. Drawing from critical ethnographic research in the favelas of Vitoria, Brazil, this study sheds light on the social and cultural practices that happen in these establishments. In addition, it highlights the complex relationship between the LAN Houses and the government.